Analisis Kelayakan Usaha Penangkaran Pembibitan Kelapa Sawit di Kecamatan Meliau Kabupaten Sanggau - Darwin Adi Putra Chin; Adi Suyatno; Maswadi (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to assess the feasibility of the oil palm nursery business in Meliau District, Sanggau Regency. In this study, the sampling method applied was saturated sampling, selecting a total of 10 respondents. The data sources comprised both primary and secondary data, which were then analyzed through descriptive analysis, revenue analysis, cost analysis, income analysis, and an assessment of business feasibility. Based on the calculations conducted by the author, the average total production cost is Rp 6,247,330 per hectare per farmer. During one production period, the average revenue earned by farmers is Rp 9,520,000 per farmer per period. The average income from the oil palm business in Meliau Sub-district, Sanggau District, is IDR 3,272,670 per hectare per farmer per period, which is then reduced by a mortality rate of 20%. Therefore, the net income of farmers is Rp 2,618,405 per hectare per farmer per period, which is obtained from the calculation of the R/C ratio, which is 1.57, meaning that the oil palm seedling breeding business in Meliau District, Sanggau Regency, is feasible and can be developed in the coming years.